Bioinformatic challenges for the next decade(s) - Eisenberg, David (The Royal Society, 2006)
The science of bioinformatics has developed in the wake of methods to determine the sequences of the informational macromolecules—DNAs, RNAs and proteins. But in a wider sense, the biological world depends in its every process on the transmission of information, and hence bioinformatics is the fundamental core of biology. We here give a consideration of some of the key problems of bioinformatics in the coming decade, and perhaps longer.